2021
DOI: 10.1142/s021833902150025x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Additional Food on Predator–prey Interactions With Water-Level Fluctuation

Abstract: Significant variations of the water-level of the lake can have a strong impact on the persistence of species. Indeed, when the water-level is low, during the autumn, the contact between the predator and the prey is more frequent, and the predation increases. Conversely, when the water-level is high, in the spring, it is more difficult for the predator to find a prey and the predation decreases. In this paper, we consider a seasonally varying predator–prey model to study the influence of water-level variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The benefit of considering the above forms of q(t) and l(t) is that these time dependent parameters q(t) and l(t) have high and low seasons both in the periods where sin(𝜔t) is positive and negative, respectively [52,53]. Here, the parameters q 1 (0 < q 1 < q) and l 1 (0 < l 1 < l) decide the strength of seasonal forcing in q(t) and l(t), respectively.…”
Section: Simulation Results Of System (34)mentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of considering the above forms of q(t) and l(t) is that these time dependent parameters q(t) and l(t) have high and low seasons both in the periods where sin(𝜔t) is positive and negative, respectively [52,53]. Here, the parameters q 1 (0 < q 1 < q) and l 1 (0 < l 1 < l) decide the strength of seasonal forcing in q(t) and l(t), respectively.…”
Section: Simulation Results Of System (34)mentioning
confidence: 99%
“…We consider the sinusoidal forms of qfalse(tfalse)$$ q(t) $$ and lfalse(tfalse)$$ l(t) $$: rightq(t)=q+q1sin(ωt),l(t)=l+l1sin(ωt).$$ q(t)&amp;amp;amp;#x0003D;q&amp;amp;amp;#x0002B;{q}_1\sin \left(\omega t\right),l(t)&amp;amp;amp;#x0003D;l&amp;amp;amp;#x0002B;{l}_1\sin \left(\omega t\right). $$ The benefit of considering the above forms of qfalse(tfalse)$$ q(t) $$ and lfalse(tfalse)$$ l(t) $$ is that these time dependent parameters qfalse(tfalse)$$ q(t) $$ and lfalse(tfalse)$$ l(t) $$ have high and low seasons both in the periods where sinfalse(ωtfalse)$$ \sin \left(\omega t\right) $$ is positive and negative, respectively [52, 53]. Here, the parameters q10.1emfalse(0<q1<qfalse)$$ {q}_1\kern0.1em \left(0&amp;amp;lt;{q}_1&amp;amp;lt;q\right) $$ and l10.1emfalse(0<l1<lfalse)$$ {l}_1\kern0.1em \left(0&amp;amp;lt;{l}_1&amp;amp;lt;l\right) $$ decide the strength of seasonal forcing in qfalse(tfalse)…”
Section: Numerical Observationsmentioning
confidence: 99%
“…Let c denotes the degree of hunting cooperation among the predator species. By considering Michaelis-Menten type harvesting, several researchers have showed that harvesting of species has a strong impact on the population dynamics [ 57 , 58 ]. Here, we introduce nonlinear harvesting of predators by the term where q is the catching capability coefficient, E is the effort applied to harvest the predators, and and are positive constants.…”
Section: The Autonomous Modelmentioning
confidence: 99%
“…The role of harvesting in a disease-dominated predator-prey system was explored by Sk and Pal [6]. Sarkar et al [13] investigated the impact of additional foods in a predator-prey system within aquatic ecosystems, considering nonlinear harvesting of predators alongside water level fluctuations.…”
mentioning
confidence: 99%